Nitrogen Fixation at the Edges of Boron Nitride Nanomaterials: Synergy of Doping - Choutipalli, Venkata Surya Kumar; Esackraj, Karthikraja; Subramanian, Venkatesan (Frontiers in Chemistry, 2022)
Synthesis of ammonia at ambient conditions is very demanding yet challenging to achieve due to the production of ammonia fuel, which is considered to be a future fuel for sustainable energy. In this context, computational studies on the catalytic activity of the edge sites of boron nitride nanomaterials for possible nitrogen reduction into ammonia have been investigated. Geometrical and electronic properties of zigzag and armchair B-open edges of BN sheet (BOE) models have been unraveled to substantiate their catalytic nature. Results reveal that BOE sites exhibit very high potential determining steps (PDS) of 2.0 eV. Doping of carbon (C) at the nitrogen center, which is vicinal to the BOE site reduces the PDS of the N2 reduction reaction (NRR) (to 1.18–1.33 eV) due to the regulation of charge distribution around the active BOE site. Further, the NRR at the C doped at various edge sites of a boron nitride sheet (BNS) has also been studied in detail. Among the 12 new C-doped defective BNS models, 9 model catalysts are useful for nitrogen activation through either chemisorption or physisorption. Among these, ZCN, ACN, and ZCBV models are efficient in catalyzing NRR with lower PDS of 0.86, 0.88, and 0.86 eV, respectively. The effect of carbon doping in tuning the potential requirements of NRR has been analyzed by comparing the relative stability of intermediates on the catalyst with and without carbon doping. Results reveal that C-doping destabilizes the intermediates compared to non-doped systems, thereby reducing the possibility of catalyst poisoning. However, their interactions with catalysts are good enough so that the NRR activity of the catalyst does not decrease due to C-doping.